Conformal field theory for the superstring in a Ramond-Ramond plane wave background - Berkovits, Nathan [UNESP] (Springer Nature, 2002)
A quantizable worldsheet action is constructed for the superstring in a super-symmetric plane wave background with Ramond-Ramond flux. The action is manifestly invariant under all isometries of the background and is an exact worldsheet conformal field theory. © SISSA/ISAS 2002.
Keywords: Penrose limit and pp-wave background; Superstrings and Heterotic Strings